Association of activities related to pesticide exposure on headache severity and neurodevelopment of school-children in the rural agricultural farmlands of the Western Cape of South Africa. (January 2021) - Chetty-Mhlanga, Shala; Fuhrimann, Samuel; Basera, Wisdom; Eeftens, Marloes; Röösli, Martin; Dalvie, Mohamed Aqiel
Highlights: Study of 1001 school-going children from three agricultural areas of South Africa. Effects of pesticide related activities of children has rarely been investigated. Cognitive performance was assessed with a validated test battery on a tablet. Consistent associations between pesticide exposure and headache. Suggestive, but mostly non-significant, negative associations with cognition. Abstract: Objective: Children and adolescents living in agricultural areas are likely to be exposed to mixtures of pesticides during their daily activities, which may impair their neurodevelopment. We investigated various such activities in relation to headache severity and neurodevelopment of school-children living in rural agricultural areas in the Western Cape of South Africa. Method: We used baseline date from 1001 school-children of the Child Health Agricultural Pesticide Cohort Study in South Africa (CapSA) aged 9–16 from seven schools and three agriculture areas in the Western Cape. Questionnaires were administrated to assess activities related to pesticide exposure and health symptoms addressing four types of activities: 1) child farm activities related to pesticide handling, 2) eating crops directly from the field, 3) contact with surface water around the field, and 4) seen and smelt pesticide spraying activities. Neurocognitive performance across three domains of attention, memory and processing speed were assessed by means of an iPad-based cognitive assessment tool, Cambridge Automated NeuroPsychological Battery (CANTAB). Headache severity was enquired using a standard Headache Impact Test (HIT-6) tool. Cross-sectional regression analysis was performed. Results: About 50% of the cohort report to have ever been engaged in activities related to pesticide exposure including farm activities, eating crops directly from the field and leisure activities. Headache severity score was consistently increased in relation to pesticide-related farm activities (score increase of 1.99; 95% CI: 0.86, 3.12), eating crops (1.52; 0.41, 2.67) and leisure activities of playing, swimming or bathing in nearby water (1.25; 0.18, 2.33). For neurocognitive outcomes, an overall negative trend with pesticide exposure-related activities was observed. Among others, involvement in pesticide-related farm activities was associated with a lower multi-tasking accuracy score (−2.74; −5.19, −0.29), while lower strategy in spatial working memory (−0.29; −0.56; −0.03) and lower paired associated learning (−0.88; −1.60, −0.17) was observed for those who pick crops off the field compared to those who do not pick crops off the field. Eating fruits directly from the vineyard or orchard was associated with a lower motor screening speed (−0.06; −0.11, −0.01) and lower rapid visual processing accuracy score (−0.02; −0.03, 0.00). Conclusions: Children who indicate activities related to pesticide exposure may be at higher risk for developing headaches and lower cognitive performance in the domains of attention, memory and processing speed. However, self-reported data and cross-sectional design are a limitation. Future research in CapSA will consider pesticide exposure estimations via urinary biomarkers and longitudinal assessment of cognitive functions.